2021
DOI: 10.3389/fmars.2021.612386
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Dissolved Organic Matter Composition in a Patagonian Fjord Affected by Glacier Melt Inputs

Abstract: Biogeochemical processes in fjords are likely affected by changes in surrounding glacier cover but very little is known about how meltwater directly influences dissolved organic matter (DOM) in fjords. Moreover, the data available are restricted to a handful of northern hemisphere sites. Here we analyze seasonal and spatial variation in dissolved organic carbon (DOC) concentration and DOM composition (spectrofluorescence, ultrahigh resolution mass spectrometry) in Baker-Martinez Fjord, Chilean Patagonia (48°S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 126 publications
(200 reference statements)
0
2
1
Order By: Relevance
“…The result indicated that FDOM H in glacial meltwater may be an important determinant of the dFe concentration in Areas A and C. The BIX values suggest that FDOM H in Inglefield Bredning is freshly produced DOM. Although a high contribution of microbially derived DOM in glacial meltwaters has been reported in elsewhere (e.g., Kellerman et al, 2020;Marshall et al, 2021;Pain et al, 2020), its contribution in our studied fjord is unclear. The absence of a significant correlation between dFe and FDOM H in the plume water of Area B (Figure 4a) was probably due to the high concentration of suspended sediment (Figure 5l) and removal of FDOM H by adsorption onto sediment particles.…”
Section: Distributions Of Doc Fdom H and Dfecontrasting
confidence: 53%
“…The result indicated that FDOM H in glacial meltwater may be an important determinant of the dFe concentration in Areas A and C. The BIX values suggest that FDOM H in Inglefield Bredning is freshly produced DOM. Although a high contribution of microbially derived DOM in glacial meltwaters has been reported in elsewhere (e.g., Kellerman et al, 2020;Marshall et al, 2021;Pain et al, 2020), its contribution in our studied fjord is unclear. The absence of a significant correlation between dFe and FDOM H in the plume water of Area B (Figure 4a) was probably due to the high concentration of suspended sediment (Figure 5l) and removal of FDOM H by adsorption onto sediment particles.…”
Section: Distributions Of Doc Fdom H and Dfecontrasting
confidence: 53%
“…However, DOC losses are strongly related to microbial activity only when the soil's ability to stabilize soluble carbon is low (Silveira, 2005). Due to its varying molecular weight and polarity, DOC is of considerable practical interest as it could serve as a sensitive indicator of changes in the soil ecosystem (Marshall et al, 2021), especially with its ability to complex different types of pollutants (Reyes and Crisosto, 2016). The low DOC exports out of peat systems contribute to maintaining low carbon exchanges with the external environment.…”
Section: Dissolved Organic Carbonmentioning
confidence: 99%
“…In addition, carbon losses occur in the dissolved form by leaching due to biodegradation and photochemistry/photooxidation (Reyes and Crisosto, 2016). Carbon losses, often with CO2 emission, can shift the carbon balance of peatlands from the sink to the source (Marshall et al 2021).…”
Section: Introductionmentioning
confidence: 99%